WARISAN SENI ISLAM DALAM KAJIAN ILMU KALIGRAFI ARAB - Adila Umniati Ulfa; Lely Triastuti; Ruwiyah Zamzam (Jurnal Ekshis, 2025)
Calligraphy education is an effective means of preserving and strengthening the identity of Islamic art. In conclusion, calligraphy education has a very important role in maintaining the heritage of Islamic art. Through calligraphy education, the art of Islamic calligraphy can continue to live and develop, understanding of Arabic script and Arabic language can be enriched, and the social and economic impact of the art of calligraphy can be utilized. Thus, calligraphy education is key to ensuring that this valuable Islamic artistic legacy remains alive and is passed on to future generations. The method used is based on collecting and analyzing data sourced from literature, books, journal articles, scientific publications and other relevant sources. Calligraphy education in maintaining the heritage of Islamic art is very important, because calligraphy, as the art of beautiful writing using Arabic script, has been an integral part of Islamic culture and identity for centuries. The art of calligraphy not only has high aesthetic value, but also has deep spiritual and symbolic meaning in the Islamic religion. Keywords: Calligraphy, Islamic Artistic Heritage